Genetic parameters of wound healing in patients with neuropatic diabetic foot ulcers - Ekaterina L. Zaitseva (Endocrinology Research Centre, 2017)
Background. Tissue repair processes are impaired in diabetic foot ulcers (DFUs). Previous research has shown that glycaemic control, cytokines and growth factors play an important role in wound healing. Emerging evidence also suggests that genes play a role via their regulation of cell proliferation, collagen synthesis and granulation tissue formation. Aim. To evaluate collagen genes expression in different stages of wound healing in patients with DFUs. Materials and methods. Prospective study included four patients with neuropathic DFUs after surgical debridement. Tissue samples were taken for morphological and genetic tests on days 0, 10 and 15 of local treatment to evaluate expression of collagen genes (i.e. COL1A1, COL1A2, COL3A1) and to perform morphological tests. Results. The present study confirmed that the size of wounds decreased by 8.8 ± 7% after 10 days of local treatment and by 18.3 ± 8% after 15 days of local treatment. According to histological examination of wound biopsies at day 10, all patients showed a tendency for lower levels of inflammatory infiltrate, increased number of fibroblast-like cells, presence of maturing granulation tissue and emergence of connective tissue fibres. After 15 days, we detected inflammatory infiltration in the wounds, despite the formation of mature granulation tissue. According to results of genetic analysis on day 10 of local wound treatment, we found a tendency for increased expression of collagen genes relative to the baseline: COL1A1 increased by 3.2 ± 1.3 times, COL1A2 by 2.0 ± 1.0 times and COL3A1 by 1.25 ± 1.1 times. On day 15 of local treatment, in contrast, we found a tendency for decreased expression of COL1A1, COL1A2 and COL3A1 relative to the baseline (1.7 ± 0.6, 2.5 ± 2 and 20.0 ± 3 times, respectively). Conclusions. The expression of collagen genes (COL1A1, COL1A2, COL3A1) is more pronounced in proliferation phase and is subsequently reduced towards the end. These data were confirmed by morphological study and clinical pictures.